GREEN ACCOUNTING, ENVIROMENTAL PERFORMANCE AND CORPORATE SOCIAL RESPONTIBILITY PRACTICES AS DETERMINANTS OF FIRM VALUE IN INDONESIA’S MINING SECTOR - Yana, Fitri; Harianto, Syawal; Herwinsyah, Reynold (Universitas Sultanah Nahrasiyah, 2025)
This research aims to examine the effect of implementing Green Accounting, Environmental Performance, and Corporate Social Responsibility on Company Value in mining sector companies listed on the Indonesia Stock Exchange for the 2020-2023 period. The independent variables used are Green Accounting, Environmental Performance, and Corporate Social Responsibility. while the dependent variable is Company Value. There are 63 mining sector companies as a population listed on the Indonesian Stock Exchange. The research sample using purposive sampling obtained 11 samples. This research uses a multiple linear regression analysis method using panel data. The research results show that the application of green accounting has a positive and significant effect on company value, environmental performance has a positive and significant effect on company value, while corporate social responsibility has no effect on company value. The contribution of all independent variables Implementation of Green Accounting, Environmental Performance, and Corporate Social Responsibility to Company Value is 32.3%, while the remaining 67.7% can be explained by other variables outside this research.